Spontaneous poisoning by larvae of perreyia flavipes (Pergidae) in pigs in the state of Santa Catarina Intoxicação espontânea por larvas de Perreyia flavipes (Pergidae) em suínos no Estado de Santa Catarina - Jonck F.* (2010)
The study reports an outbreak of spontaneous poisoning by Perreyia flavipes in pigs. The outbreak occurred at the end of May 2009, in the municipality of Urubici, plateau of Santa Catarina, Brazil. The farm had about 50 pigs reared extensively and 10 animals got sick. The clinical signs were anorexia, apathy, constant movement of the head and hitting the ears, difficulty to walk and stagger, gnashing of teeth and agitation that increased with noise and movement nearby. At necropsy, pronounced hepatic lobular pattern and P. flavipes larvae mixed with the stomach content were observed. Microscopically, hepatocellular centrilobular to diffuse coagulation necrosis with severe congestion and hemorrhage was observed, with vacuolar degeneration in one or two layers of hepatocytes in the portal zones. Clinical signs, epidemiology and lesions in the pigs were characteristic of toxic hepatitis by larvae of P. flavipes.